Teaching Skills of Teacher in Increasing Student Learning Interest - Sariaman Gultom; Ahmad Fakhri Hutauruk; Andres M. Ginting (Budapest International Research and Critics University, 2020)
Lack of student interest in learning results in pre-determined learning goals not being achieved. The teacher must work hard to find new breakthroughs so students are interested in learning. In addition to implementing a good work ethic, a teacher must also have skills in teaching as to achieve learning objectives in accordance with curriculum requirements. This research involves qualitative research method. The data analysis techniques used are: data reduction, data presentation and drawing conclusions / verification. The result of the study indicate that a teacher must have several teaching skills, namely: (1) questioning skills, (2) reinforcement skills, (3) variation skills, (4) explaining skills, (5) learning skills opening and closing, (6) small group discussion guiding skills, (7) small classroom management skills, and (8) small group and individual teaching skills.